1996
DOI: 10.1007/bf00154612
|View full text |Cite
|
Sign up to set email alerts
|

Ester synthesis in aqueous media in the presence of various lipases

Abstract: SITMMARYThe ability of seven lipase preparations to catalyse methyl ester synthesis in aqueous media was compared and the synthesis reaction (esterification or alcoholysis) determined. Three behaviours were observed: three enz)qnes catalysed ester synthesis by esterification of free fatty acids and one enzyme catalysed alcoholysis but the other three lipases did not catalyse a net ester synthesis under the conditions tested. The three groups also differed by the influence of methanol on the hydrolysis reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 8 publications
(6 reference statements)
1
32
0
Order By: Relevance
“…In the samples obtained at the end of the first batch with no water addition, the largest differences in the acylglycerol profiles were (i) the production of acylglycerols of ECN equal or lower than 30 (peaks 2-5) and of ECN 44 (peaks 15 and 16) and (ii) the consumption of peak 8 (ECN 36) and acylglycerols of ECN 48 (peaks [20][21][22]. In this set of experiments, the acylglycerol profiles of interesterified blends from batches 2-4 were not very different from that of the original blend (data from batches 3 and 4 are not shown).…”
Section: Batch Operational Stabilitymentioning
confidence: 99%
“…In the samples obtained at the end of the first batch with no water addition, the largest differences in the acylglycerol profiles were (i) the production of acylglycerols of ECN equal or lower than 30 (peaks 2-5) and of ECN 44 (peaks 15 and 16) and (ii) the consumption of peak 8 (ECN 36) and acylglycerols of ECN 48 (peaks [20][21][22]. In this set of experiments, the acylglycerol profiles of interesterified blends from batches 2-4 were not very different from that of the original blend (data from batches 3 and 4 are not shown).…”
Section: Batch Operational Stabilitymentioning
confidence: 99%
“…There are a few studies on lipase-catalysed esterifications in aqueous media, all involving hydrophobic long-chain fatty acids (C 16 and above), polar and non-polar C 1-10 alcohols (Ishii et al, 1990;Boutur et al, 1995;Lecointe et al, 1996). Nonetheless, there is still a lack of understanding about esterification and alcoholysis in aqueous systems.…”
Section: Bioproduction Of Isoamyl Octanoate By Lipase Palatase In Bufmentioning
confidence: 99%
“…With such lipases, a so-called transesterification can also be obtained through the hydrolysis of an ester substrate followed by the re-esterification of the released fatty acids with an alcohol acceptor. A direct alcoholysis of an ester substrate can also be catalyzed by classical lipases but this is not the main reaction in aqueous conditions with high a w [9,14]. However, it has been shown that some lipases, described as lipases/acyltransferases, are able to catalyze alcoholysis preferentially to hydrolysis even in the presence of low alcohol concentration and high a w (N0.9).…”
Section: Introductionmentioning
confidence: 97%
“…One is the esterification of free fatty acids, where a lipase is used to catalyze reverse hydrolysis to reach the thermodynamic equilibrium of the hydrolysis/ esterification reaction. This has been successfully used in various studies, for example with lipases from Candida deformans, Mucor miehei, Rhizopus delemar, Pseudomonas fluorescens, Rhizopus arrhizus or with lipase A from P. antarctica [9][10][11][12][13][14][15]. With such lipases, a so-called transesterification can also be obtained through the hydrolysis of an ester substrate followed by the re-esterification of the released fatty acids with an alcohol acceptor.…”
Section: Introductionmentioning
confidence: 99%